2004
DOI: 10.1523/jneurosci.2695-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Properties of Mutant Nav1.7 Sodium Channels in a Painful Inherited Neuropathy

Abstract: Although the physiological basis of erythermalgia, an autosomal dominant painful neuropathy characterized by redness of the skin and intermittent burning sensation of extremities, is not known, two mutations of Na v 1.7, a sodium channel that produces a tetrodotoxinsensitive, fast-inactivating current that is preferentially expressed in dorsal root ganglia (DRG) and sympathetic ganglia neurons, have recently been identified in patients with primary erythermalgia. Na v 1.7 is preferentially expressed in small-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
295
3
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(332 citation statements)
references
References 42 publications
29
295
3
5
Order By: Relevance
“…All these changes would be expected to increase the excitability of nociceptive dorsal root ganglion neurons harboring the mutation, thus contributing to the pain in IEM (8,17). Slow inactivation, on the other hand, was enhanced in the S241T mutant channels, similar to previously reported IEM mutations (8,16,18), but its contribution to the pathophysiology of erythromelalgia is not known at this time. This change would theoretically render mutations expressing DRG neurons hypoexcitable.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…All these changes would be expected to increase the excitability of nociceptive dorsal root ganglion neurons harboring the mutation, thus contributing to the pain in IEM (8,17). Slow inactivation, on the other hand, was enhanced in the S241T mutant channels, similar to previously reported IEM mutations (8,16,18), but its contribution to the pathophysiology of erythromelalgia is not known at this time. This change would theoretically render mutations expressing DRG neurons hypoexcitable.…”
Section: Discussionsupporting
confidence: 88%
“…Enhanced slow inactivation has been observed for several IEM mutations (16,18), including those showing increased neuronal excitability in dorsal root ganglion neurons (8,17,18). S241T enhances steady-state slow inactivation and shifts the V1 ⁄ 2 by Ϫ12.3 mV from Ϫ78.4 Ϯ 2.1 mV (n ϭ 21) for Nav1.7 R to Ϫ90.7 Ϯ 1.1 mV (n ϭ 12) for S241T (p Ͻ 0.001) (Fig.…”
Section: S241t Lowers Threshold For Activation Slows Deactivation Amentioning
confidence: 97%
“…72 Transfection of HEK293 cells with two different mutations of human DNA for Na V 1.7 that are associated with familial autosomal erythermalgia showed that the mutated channel produced a hyperpolarizing shift in activation, slowed deactivation of the channel and markedly increased the ramp current, with the net effect being a marked hyperexcitation of the cells. 73 These alterations would be consistent with enhanced nociception and sympathetic activity and could account for the etiology of erythermalgia. 73 More recently, voltage clamp studies performed on transfected mouse DRG cells showed that the human mutations lowered the thresholds for generation of action potentials and repetitive firing, thus provoking high-frequency firing of nociceptive small diameter sensory neurons in the DRG.…”
Section: Na V 13mentioning
confidence: 82%
“…73 These alterations would be consistent with enhanced nociception and sympathetic activity and could account for the etiology of erythermalgia. 73 More recently, voltage clamp studies performed on transfected mouse DRG cells showed that the human mutations lowered the thresholds for generation of action potentials and repetitive firing, thus provoking high-frequency firing of nociceptive small diameter sensory neurons in the DRG.…”
Section: Na V 13mentioning
confidence: 82%
“…Primary erythromelalgia and paroxysmal extreme pain disorder among painful inherited neuropathies are caused by several mutations in the SCN9A gene [4,5]. Met1627Lys mutation has been previously described in a sporadic case of paroxysmal extreme pain disorder from France [1], and then reported in an English family [2].…”
Section: Discussionmentioning
confidence: 99%